Validation of the English version constitution in Chinese Medicine Questionnaire (CCMQ) among young adults in Malaysia - Fl, Ng; CN, Foo; SY, Yap; YM, Lim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Constitution in Chinese Medicine Questionnaire (CCMQ) is widely used as a self-administered health instrument. It was used as the guiding tool for prognosis, prevention and treatment of various diseases. This study aims to validate an English version of the Constitution in Chinese Medicine Questionnaire (CCMQ) in Malaysia, which is comprised of nine domains with a total of 67 questions. The survey was conducted in three phases. Phase one involved translation and adaption where the Chinese version of the survey instrument was translated into the English version. In phase two, a Delphi was used to review, amend and validate the translated English version; and in phase three, 114 subjects (aged 18 to 30 years old) were included in the confirmatory factor analysis to determine its psychometric properties. The construct validity analysis of CCMQ showed a good fit for the hypothesised models. Composite reliability (CR) values ranging from 0.869 to 0.908, and average variance extracted (AVE) values ranged from 0.647 to 0.764, indicating good internal consistency reliability and convergent validity, respectively. The heterotrait-monotrait ratio of correlations (HTMT) values obtained for all the domains ranging from 0.151 to 0.652, which fulfilled the criteria of discriminant validity. The English version of the CCMQ was the first statistically validated instrument in Malaysia. It is a reliable and valid instrument for traditional Chinese medicine body constitution (TCMBC) study. Future research is needed to validate the CCMQ as a predicting tool in health-related outcome studies.